A Review of PSAK No. 1 (2009 Revision): Presentation of Financial Statements and Its Difference from PSAK No. 1 (1998 Revision) - Any Eliza (Jurnal Ilmiah ESAI, 2012)
As the implementation of convergence to IFRS, Indonesia has fully adopted IAS 1: Presentation of Financial Statements per January 1, 2009 into PSAK No. 1 (2009 Revision): Presentation of Financial Statements. PSAK No. 1 (2009 Revision) revised PSAK No. 1 (1998 Revision). Major differences involve the terms used, the complete components of financial statements, the information presented on financial statements, the presentation of extraordinary items, the statements of comprehensive income, and the time to publish financial statements. Keywords:Â  convergence to IFRS, PSAK No. 1 (2009 Revision): Presentation of financial statements, the differences between PSAK No. 1 (1998 Revision) and PSAK No. 1 (2009 Revision)